2016
DOI: 10.1002/pd.4883
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of intracranial translucency in detecting spina bifida: a systematic review and meta-analysis

Abstract: Intracranial translucency had low diagnostic accuracy in prediction of open spina bifida, thus questioning its role as a screening marker for open SB in an unselected population. When looking at the individual study data, it appears that IT assessment for open SB prediction can be affected by a high rate of false positive results potentially leading to unnecessary parental anxiety. © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 33 publications
2
20
0
1
Order By: Relevance
“…In our study, IT measurement < 5th percentile was the poorest‐performing parameter in the detection of open spina bifida identifying just over 50% of the cases, which goes in line with a wide range and variety of published data . Performance of IT has been recently evaluated in a systematic review and meta‐analysis including nine studies, three with prospective and six with retrospective design.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In our study, IT measurement < 5th percentile was the poorest‐performing parameter in the detection of open spina bifida identifying just over 50% of the cases, which goes in line with a wide range and variety of published data . Performance of IT has been recently evaluated in a systematic review and meta‐analysis including nine studies, three with prospective and six with retrospective design.…”
Section: Discussionmentioning
confidence: 93%
“…Nonvisualization of IT (seven studies), IT < 5th percentile (one study) and IT < 1st percentile (one study) were the criteria for suspecting of spina bifida. The overall DR was 53.5% (95% CI, 42.4‐64.3) …”
Section: Discussionmentioning
confidence: 93%
“…Chaoui et al 1,2 were the first to suggest that assessment of the fourth ventricle, also called intracranial translucency, at the time of the 11-13-week ultrasound scan could be a method of early screening for open spina bifida (OSB). Subsequent studies have confirmed this observation [3][4][5] and have also reported an association between other posterior fossa abnormalities and OSB, including increased diameter of the brainstem (BS) and abnormal BS diameter-to-BS-to-occipital-bone distance (BS/BSOB) ratio [6][7][8] , obliteration of the cisterna magna [9][10][11][12][13][14] , and posterior displacement of the aqueduct of Sylvius 15 . These ultrasound features are almost invariably present in first-trimester fetuses with OSB and are thought to be the result of early backward displacement of the posterior brain as a consequence of chronic leakage of cerebrospinal fluid through the spinal defect and hypotension of the cerebral ventricular system.…”
Section: Introductionmentioning
confidence: 83%
“…Evaluation of the 4th ventricle, also referred to as intracranial transparency (IT), and examination of the brain stem can result in early detection of open spina bifida in the first-trimester examination [15,16]. In a meta-analysis including more than 21 000 fetuses, a sensitivity of 53.5 % and a specificity of 99.7 % were calculated [17].…”
Section: Early Diagnosis Of Anomaliesmentioning
confidence: 99%